An Imine-Based Route to Polycyclic Chlorinated ε-Lactams by Formation of C–C Bonds as Key Steps - Brockmeyer, Fabian; Stalling, Timo; Martens, Jürgen (Synthesis, 2012)
A two-step sequence for the conversion of heterocyclic imines to saturated and unsaturated polycyclic chlorinated ε-lactams is disclosed. In the first step, an acyl chloride addition followed by a substitution is used to achieve unsaturated methoxyamides. The final lactamization to two different classes of polycyclic ε-lactams via formation of a C–C bond is realized by the use of metal chlorides as Lewis acid and as a source of chloride. The potential of the ε-lactams in subsequent reactions is demonstrated by an elimination reaction.
Keywords: heterocycles; imines; lactams; ring closure; ring contraction; Schiff bases